2018
DOI: 10.1016/j.ijsu.2018.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Nutritional Risk Index as a prognostic factor in patients with esophageal squamous cell carcinoma –retrospective cohort study

Abstract: GNRI is considered to be a useful prognostic factor in patients with ESCC undergoing esophagectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 28 publications
4
49
0
Order By: Relevance
“…NRI is another commonly used nutritional indicators which integrated with objective measurements of nutritional status including albumin, height and weights. The study also found that lower levels of NRI was associated with poor survival in oral cancer patients, which is consistent with the previous findings in gastric cancer [17] esophageal squamous cell carcinoma [14] and liver cancer [18].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…NRI is another commonly used nutritional indicators which integrated with objective measurements of nutritional status including albumin, height and weights. The study also found that lower levels of NRI was associated with poor survival in oral cancer patients, which is consistent with the previous findings in gastric cancer [17] esophageal squamous cell carcinoma [14] and liver cancer [18].…”
Section: Discussionsupporting
confidence: 92%
“…Traditional nutritional indicators such as body mass index (BMI) and serum albumin (ALB) have been widely used in clinical to assess the nutritional status of the cancer patients and have been shown to be associated with the prognosis of a variety of tumors such as rectal cancer, head neck, oral cancer and gynecologic malignancies [9][10][11][12][13]. In addition to BMI and ALB, two comprehensive indicators prognostic nutritional index (PNI) which includes albumin and lymphocyte and nutritional risk index (NRI) which combines weight, height and serum albumin levels, have also been reported as simple but sensitive methods that can objectively assess the nutritional status of cancer patients and predict their prognosis in esophageal squamous cell carcinoma, liver cancer, lung cancer, and gastric cancer et al [11,[14][15][16][17][18][19]. However, there are few studies comprehensively explored the relationship between different nutritional indicators and prognosis of oral cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, study has shown that GNRI is a favorable predictor of muscle function in renal transplant recipients [52]. Besides, GNRI was now considerd as a novel prognostic factor for cancer patients [53,54]. These results indicate that GNRI can be a powerful predictor for clinical outcome in different diseases and may be widely used in clinical practice.…”
Section: Discussionmentioning
confidence: 95%
“…11,12 GNRI is widely used in nutritional assessment of elderly patients with chronic liver failure, chronic obstructive pulmonary disease, and cardiovascular disease. [13][14][15] Recently, many studies have found that GNRI can be used in the prognostic assessment of various malignant tumors, including renal cell carcinoma, 16,17 esophageal squamous cell carcinoma, 18 hepatocellular carcinoma, 19 and pathological stage I non-small cell lung cancer. 20 However, there is currently little research on the relationship between GNRI and outcomes in elderly CRC patients.…”
Section: Introductionmentioning
confidence: 99%